2017
DOI: 10.1021/acscombsci.6b00184
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pictet–Spengler Reaction to Indole-Based Alkaloids Containing Tetrahydro-β-carboline Scaffold in Combinatorial Chemistry

Abstract: Indole-based alkaloids are well-known in the literature for their diverse biological properties. Polysubstituted optically active tetrahydro-β-carboline derivatives functionalized on C-1 position are the common structural motif in most of the indole-based alkaloids, as well as highly marketed drugs. The stereoselective Pictet-Spengler reaction is one of the currently most important synthetic techniques used for the preparation of these privileged tetrahydro-β-carboline scaffolds. To date, there are numerous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(35 citation statements)
references
References 136 publications
0
35
0
Order By: Relevance
“…These results confirmed that both 9 and 10 could contribute to the formation of final product in the absence of catalyst. Based on these results and the reported literature, [13][14][15][16]19,25] a rationalized reaction mechanism was proposed in Scheme 4. Initially, the nitrone 2 attacked the gold-activated alkyne to form a vinylgold species II, followed by a hydrolysis/protodeauration/ 3,3-sigmatropic rearrangment/cyclodehydration sequence via intermediate III to gave the indole product V, and releasing the corresponding aldehyde simultaneously.…”
Section: Full Paper Ascwiley-vchdementioning
confidence: 66%
See 2 more Smart Citations
“…These results confirmed that both 9 and 10 could contribute to the formation of final product in the absence of catalyst. Based on these results and the reported literature, [13][14][15][16]19,25] a rationalized reaction mechanism was proposed in Scheme 4. Initially, the nitrone 2 attacked the gold-activated alkyne to form a vinylgold species II, followed by a hydrolysis/protodeauration/ 3,3-sigmatropic rearrangment/cyclodehydration sequence via intermediate III to gave the indole product V, and releasing the corresponding aldehyde simultaneously.…”
Section: Full Paper Ascwiley-vchdementioning
confidence: 66%
“…These results consisted with general tendency of Pictet-Spengler reaction and cyclization with external aldehyde. [19] Moreover, the model reaction in the presence of p-methylaniline (Scheme 3d) [24] or imines 7 (Scheme 3e) only formed the product 3 a in comparable high yields, and no corresponding annulation product with aniline or imine was detected, which suggested that the early stage of this cascade reaction, the gold-catalyzed oxoarylation step, happened in the inner-sphere. [13,14] Intend to investigate the possible [a] Unless otherwise noted, the reaction was carried out on a 0.2 mmol scale: 1 (0.3 mmol) in 1.0 PhF was slowly added to a solution of PPh 3 AuNTf 2 (7.4 mg, 5.0 mol%), and 2 (0.2 mmol) in PhF (1.0 mL) under an argon atmosphere at 0°C, and the yields are given in isolated yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pictet‐Spengler reaction (PSR), discovered in 1911, has been providing economical and direct access to a versatile collection of compound structures, including tetrahydroisoquinoline, tetrahydro‐β‐carboline and other N‐heterocycles (Figure ) . Traditionally, Brønsted acid was used as the critical catalyst for PSR.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of this venerable transformation is highlighted in several total syntheses of indole alkaloids and other biologically active compounds. 3 …”
mentioning
confidence: 99%